George Herbert's Lyrics - Stein, Arnold (Arnold Sidney), 1915-2002 (Book collections on Project MUSE., 1968)
The main purpose of this book is to demonstrate that George Herbert is one of the great masters of lyric poetry. Stein discusses Herbert's diction, imagery, syntax, and rhythm in light of his organization of the imaginative materials of time and self-consciousness and in light of his development of a rhetoric through which he could master the intimacies of personal failure and (what is far more difficult) express in language convincingly sincere states of positive religious achievement.